Synthesis and SAR studies of analogues of 4-(3, 3-dimethyl-butyrylamino)-3, 5-difluoro-N-thiazol-2-yl-benzamide (Lu AA41063) as adenosine A2A receptor ligands with improved aqueous solubility. Issue 6 (15th March 2015) - Mikkelsen, Gitte Kobberøe; Langgård, Morten; Schrøder, Tenna Juul; Kreilgaard, Mads; Jørgensen, Erling B.; Brandt, Guillaume; Griffon, Yann; Boffey, Ray; Bang-Andersen, Benny
Graphical abstract: Abstract: An adenosine A2A receptor antagonist may be useful for the treatment of Parkinson's disease. Synthesis and structure–activity studies starting from 4-(3, 3-dimethylbutyrylamino)-3, 5-difluoro- N -thiazol-2-yl-benzamide (Lu AA41063, 4 ) led to a novel series of human (h) A2A receptor antagonists with improved aqueous solubility. Compound22 was identified as a key representative from the series, displaying submicromolar hA2A receptor affinity and excellent aqueous solubility. Compound22 also displayed good in vitro pharmacokinetic properties and is considered a good starting point for further lead optimisation toward hA2A receptor antagonists with improved druggability properties.